Cause of Leave Against Medical Advice (LAMA) in Paediatric Wards in Chittagong Medical College Hospital - Jabed Bin Amin Chowdhury, Muhammad; Nahar, Kamrun; Choudhury, Zabeen; Kanti Das, Aparup; Humaida Hasan, Syeda; Shah Alam, Md; Chowdhury, Munmun; Chowdhury, Dhiman; Musa Meah, Mohammad; Chowdhury, Pranab (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2024)
Background: Leaving Against Medical Advice (LAMA) is a common but undesirable clinical situation seen worldwide. This study aimed to determine the prevalence of LAMA in a pediatric setting in Bangladesh and to examine the characteristics of these patients and the reasons for their LAMA. Materials and methods: This descriptive study was carried out between October 2022 and December 2022 and assessed LAMA children from pediatric wards at the Chittagong Medical College Hospital, Chattogram, Bangladesh. Patients’ sociodemographic, disease characteristics, length of stay and reasons for their LAMA were recorded accordingly in a LAMA form. Results: A total of 8,051 children were admitted in the three months period and 227 (3.4%) children got LAMA. Out of 227 LAMA cases, 111 patients (48.9%) were <1 year old, 86 patients (37.9%) were 1–5 years old and 30 patients (13.8%) were >5 years old, and 58.5% were male. The median hospital stay was 26 hours (Range: 2 hours-15 days). Social issues like having other small siblings at home followed by dissatisfaction with care like sharing one bed among multiple patients were the most cited reasons for LAMA (21.1% and 18.9%, respectively). Financial reasons were reported by 17 (7.5%) of the patients. Conclusion: Though low observed prevalence of LAMA suggests good medical practice at the study site, the policy makers and service providers should be more responsive to initiate effective measures to further improve the quality of health care services. Chatt Maa Shi Hosp Med Coll J; Vol.22 (2); July 2023; Page 64-67